Organisational support to overcome the challenges of extended absences of officers in the SANDF - Harmse, Adele; O'Neil, Sumari; Strasheim, Arien (Scientia Militaria - South African Journal of Military Studies, 2022)
Generally, military members are often required to work away from home, resulting in extended absences from their families. International studies have shown the effects of extended absences to be severe and associated with long-term social, emotional and behavioural challenges. Longer and more frequent absences negatively affect member morale and could result in military members terminating their employment sooner than planned to maintain their personal relationships and to ensure the wellbeing of their families. The aim of the study on which this article reports was to explore and describe the experiences of extended absences on members of the South African National Defence Force (SANDF) with specific reference to organisational support to aid both the member and his or her family to cope with the challenges experienced before, during and after absences. In-depth interviews were conducted with 12 senior officers of the SANDF during 2019 and 2020, before the outbreak of the Covid-19 pandemic. The interviews focused on officers’ lived experiences of extended absences due to deployment or military training. The findings indicated that absence generally has an adverse influence on military members, not only due to the challenges they face during the absence, but mostly due to the effect it has on their families. Organisational support is not only required in terms of preparing the military member, but should be extended to include preparation prior to their absence, care for the military members and their families during the period of absence, as well as support with reintegration after the absence. The results of this study show that little support is provided by the organisation, especially during reintegration after deployment, and especially in the case of absences due to training. Organisational support during the preparation phase, during absence and with reintegration could mitigate the stress and negative experience associated with extended absences. With the aim of strengthening the capacity of the armed forces, we propose various initiatives that could assist military members and their families to cope with the additional strain of prolonged separation.